Pemetaan Spasial Kerusakan Jalan Berbasis GIS melalui KKNT Kolaborasi Lintas Negara - Paschalina Apriliani Bangkut; Joanico Luis Pereira; Eldo Marlino Fransisco da Costa (PT. Alahyan Publisher, 2026)
Road infrastructure is a vital component supporting community mobility. Maulafa District, Kupang City, East Nusa Tenggara, has several road sections with significant damage, including Jalan Fektor Funay spanning ±2,596 meters. The Collaborative Community Service Program (KKN) between Universitas Katolik Widya Mandira Kupang (UNWIRA) and Dili Institute of Technology (DIT), Timor-Leste, was implemented as a cross-national community service activity in the field of road infrastructure surveying. This activity aimed to systematically survey road damage conditions and map them using Geographic Information System (GIS) technology based on the Kernel Density Estimation (KDE) method. Field surveys identified 204 damage points consisting of potholes, cracks, rutting, edge damage, shoulder damage, and drainage damage, distributed across 26 STA segments at 100-meter intervals. KDE analysis identified three main hotspot zones of pavement damage at STA 1+700 (22 points), STA 0+800 (12 points), and STA 1+200 (10 points). This activity produced a spatial map of road conditions that can serve as a basis for prioritized handling recommendations for the Kupang City Public Works Department. This cross-national KKN program added value through academic knowledge exchange and field experience between Indonesian and Timorese students.